Kinerja Keuangan Daerah Sebelum dan Saat Pandemi Covid-19 Kabupaten dan Kota di Provinsi Kalimantan Selatan - Azizah, Marliana (PPJP ULM, 2025)
This study aims to determine the regional financial performance of 13 regencies and cities in South Kalimantan Province and the difference before and during the Covid-19 during 2018–2021. This study applies a descriptive quantitative approach with regional financial ratio analysis, which includes the fiscal decentralization ratio, the regional financial independence ratio, the effectiveness ratio, the efficiency ratio, and the compatibility ratio. The data source is Direktorat Jenderal Perimbangan Keuangan. The resulting findings are that regional financial performance in 13 regions tends to experience pressure during the covid-19 pandemic compared to the previous period. the fiscal decentralization ratio has an average of 13 regencies and has increased by 2.2%, the regional financial independence ratio has increased by 3%, the effectiveness ratio has increased by 6%, and the efficiency ratio has increased by 8.5%. The compatibility ratio consisting of the operating and the capital expenditure ratios decreased by -1.3% and -3.3%.